Kebijakan Pengelolaan Lingkungan Hidup Di Era Otonomi Daerah - Erwin Hidayah Hasibuan (DE LEGA LATA: JURNAL ILMU HUKUM, 2018)
Local governments must try to develop the potential of existing natural resources, to support the costs of sustainable development, and formally there are 5 (five) main principles of sustainable development, namely; the principle of intergenerational justice, the principle of justice in one generation, the principle of early prevention, principles of biodiversity protection and the principle of internalizing environmental costs. Related to the principle of internalizing environmental costs, the local government wants to impose on employers to seek internal funding from any expenditure that has an impact on the environment. Therefore the application of the principle of internalization of environmental costs can be interpreted as an effort to take into account the costs that must be borne by economic activity players due to the emergence of environmental losses. The principle of internalization of environmental costs underlies the content of sustainable development, and in essence aims to arouse legal awareness of economic actors to be more critical in calculating the impacts arising from their economic activities, and in the legal perspective, the principle of polluter pay must be normalized through clear arrangements, because this is a mandate of Article 42 jo. Article 43 of Law Number 32 of 2009 concerning Protection and Management of the Environment.